Bioactivities and Future Perspectives of Chaetoglobosins. (25th March 2020) - Chen, Jinhua; Zhang, Wenzhou; Guo, Qingfeng; Yu, Weijiang; Zhang, Yongna; He, Baoxia
Abstract : Chaetoglobosins belonging to cytochalasan alkaloids represent a large class of fungal secondary metabolites. To date, around 100 chaetoglobosins and their analogues have been isolated and identified over the years from a variety of fungi, mainly from the fungus Chaetomium globosum . Studies have found that chaetoglobosins possess a broad range of biological activities, including antitumor, antifungal, phytotoxic, fibrinolytic, antibacterial, nematicidal, anti-inflammatory, and anti-HIV activities . This review will comprehensively summarize the biological activities and mechanisms of action of nature-derived chaetoglobosins.